Monitoring System For Tillandsia Ornamental Plants Using Fuzzy Algorithm - Apriyani , Meyti Eka; Widianggara , Krisna; Ismail , Ade (Sinkron : jurnal dan penelitian teknik informatika, 2022)
The national floriculture industry will continue to grow, along with the interest and demand for ornamental plants by the public the author intends to design a tool in the field of communication technology by utilizing the Internet of Thing (IoT) Platform so that it can be monitored remotely by covering the cultivated land of tillandsia ornamental plants. Temperature and humidity data will be analyzed using a fuzzy algorithm. Then the system gives a callback to the actuator (relay on the water pump) to work so that the temperature and humidity reach the expected conditions stably so that the care and maintenance of tillandsia plants is optimal and maintains the water conditions of tillandsia plants. In this research, found results with an average error of 0.4% on the temperature sensor with 7 tests, 0.83% on the light sensor with 3 trials. This system has succeeded in monitoring and controlling the prototype of the IoT-based mini greenhouse condition that can monitor remotely and automatically manage the conditions of temperature, humidity, and water light intensity to remain stable, making it easier for cultivation managers to monitor land or greenhouse conditions even though they are far away from the place of cultivation for the tools and pond managers are connected to the internet network.